Koli man repairing the nets before the catch - Mumbai Archive Project Team (Jio Institute, 2024)
Rajesh Pardesi goes fishing in the morning and repairs nets in the afternoon. Every day, he repairs roughly two to three nets. As seen here, he stretches the net with his toe to make the net taut, which helps him weave the twine.